2022
DOI: 10.1519/jsc.0000000000004329
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review of Sex Differences in Muscle Strength, Endurance, Activation, Size, Fiber Type, and Strength Training Participation Rates, Preferences, Motivations, Injuries, and Neuromuscular Adaptations

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 487 publications
(942 reference statements)
3
79
1
4
Order By: Relevance
“…[25][26][27] Potential causes of this sex differences include: greater muscle mass in men which causes greater intramuscular pressures on arteries that feed the exercising muscle and thus limits blood flow and oxygen supply to the muscle; greater proportional representation of type II muscle fiber areas in men than women; and larger exercise-induced reductions in voluntary activation in men than women. 25,26,50 Nevertheless, we acknowledge that the sample sizes in the current study were small and the observed sex differences in muscle fatigability should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[25][26][27] Potential causes of this sex differences include: greater muscle mass in men which causes greater intramuscular pressures on arteries that feed the exercising muscle and thus limits blood flow and oxygen supply to the muscle; greater proportional representation of type II muscle fiber areas in men than women; and larger exercise-induced reductions in voluntary activation in men than women. 25,26,50 Nevertheless, we acknowledge that the sample sizes in the current study were small and the observed sex differences in muscle fatigability should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 75%
“…The observed sex differences of greater susceptibly of men than women to muscle fatigue from CON max ‐only and ECC max ‐CON max exercise are novel in that most studies that have observed sex differences in muscle fatigability have involved isometric rather than non ‐isometric tasks 25–27 . Potential causes of this sex differences include: greater muscle mass in men which causes greater intramuscular pressures on arteries that feed the exercising muscle and thus limits blood flow and oxygen supply to the muscle; greater proportional representation of type II muscle fiber areas in men than women; and larger exercise‐induced reductions in voluntary activation in men than women 25,26,50 . Nevertheless, we acknowledge that the sample sizes in the current study were small and the observed sex differences in muscle fatigability should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exercise protocols used do not seem to be much different, it is difficult to explain why we did not obtain similar results; however, it might be attributable to the use of free-weight exercises instead of the Smith machine. Concerning sex differences, another reason could be that women have a higher proportion of slow muscle fibers when compared to men [ 50 ]. Nevertheless, the underlying mechanisms need to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…For example, significant sex differences exist in the response to both acute exercise and chronic training adaptation ( 241 243 ), and the effects of reproductive status, endogenous and exogenous hormones, and the menstrual cycle are underappreciated not only in research studies but also in training program design and application ( 244 ). Importantly, sex differences extend to many other training-related factors, including muscle mass and strength, injuries, and even training participation rates ( 245 ). On occasion, understudied approaches can lead to detrimental outcomes, as observed for the transient hype surrounding the so-called benefits of cold-water immersion, whole body cryotherapy, and other passive recovery strategies that in certain contexts can adversely affect recovery or performance outcomes ( 246 , 247 ).…”
Section: Optimizing Training Adaptations To Enhance Athletic Performancementioning
confidence: 99%